Sharing experiences as volunteers in a peer support English language project - Pramela Krish,; Noraza Ahmad Zabidi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Setting up peer support projects is a worthy move towards student-centered learning especially at the undergraduate level. Peer support is recognized as a cooperative learning strategy that provides peer interaction. In the context of this paper, peer support refers to a voluntary project by a group of ELS students assisted by several lecturers to enhance the mastery of English language among low-proficiency undergraduate students. This paper aims to report on the journey of the students from the English Language Studies (ELS) who participated as volunteers in this peer support project for two semesters. Data for this study was collected at all three stages of the project via interviews and informal discussions with the volunteers. It reports on the experiences and challenges faced by this group of volunteers and it shares positive roles played and experienced by them. The findings also suggest that such efforts by student volunteers must be acknowledged and more efforts must be shown by students who need assistance in English to engage and benefit from their peers.